An Analysis of Efficiency and Loan Loss Provisioning Behavior in Japanese Banking - Hou, Jia Kun (2014)
This paper aims to test the determinants of loan loss provisions in Japanese banking system over the sample period 2006-2013 with respect to sample bank’s efficiency performance level (scores). In the first stage, these scores are estimated from the Stochastic Frontier Approach translog cost function. It is found that the average efficiency level for Japanese banks is 72.9% which indicates a lower efficiency gain for sample banks. In the second stage, the Generalized Method of Moments (GMM) estimator is adopted in the analysis. The empirical findings demonstrate the existence of procyclicality and capital management hypothesis whilst there is no substantial evidence of income smoothing behaviors for the sample banks. Moreover, efficiency is found to be a vital part in loan loss provisioning decision (while Z not); hence failure to incorporate it in loan loss provisions study may cause the model to be biased.